An ERP study of second language learning after childhood: effects of proficiency - Ojima, Shiro; Nakata, Hiroki; Kakigi, Ryusuke (Journal of cognitive neuroscience, 2005)
Whether there is an absolute critical period for acquiring language is a matter of continuous debate. One approach to address this issue is to compare the processes of second language (L2) learning after childhood and those of first language (L1) learning during childhood. To study the cortical process of postchildhood L2 learning, we compared event-related brain potentials recorded from two groups of adult Japanese speakers who attained either high or intermediate proficiency in English after childhood (J-High and J-Low), and adult native English speakers (ENG). Semantic anomalies embedded in English sentences evoked a clear N400 component in all three groups, with only the time course of the brain activation varying among the groups. Syntactic violations elicited a left-lateralized negativity similar to the left anterior negativity in ENG and J-High, but not in J-Low. In ENG, a P600 component was additionally found. These results suggest that semantic processing is robust from early on in L2 learning, whereas the development of syntactic processing is more dependent on proficiency as evidenced by the lack of the left-lateralized negativity in J-Low. Because early maturation and stability of semantic processing as opposed to syntactic processing are also a feature of L1 processing, postchildhood L2 learning may be governed by the same brain properties as those which govern childhood L1 learning. We argue that these processes are qualitatively similar in many respects, with only restricted domains of language processing being subject to absolute critical period effects.